Individual and mixed metal maternal blood concentrations in relation to birth size: An analysis of the Japan Environment and Children's Study (JECS). (July 2022) - Takatani, Tomozumi; Eguchi, Akifumi; Yamamoto, Midori; Sakurai, Kenichi; Takatani, Rieko; Taniguchi, Yu; Nakayama, Shoji F.; Mori, Chisato; Kamijima, Michihiro; ,
Graphical abstract: Highlights: Maternal metal exposure is associated with infant birth size. Quantile g-computation revealed that lead was the strongest negative factor for infant birth size. The BKMR analysis indicated that combined metal exposure results in an additive effect on the birth size measurements. Abstract: Background: Growth restriction in the prenatal period is a significant public health concern. Metals can negatively affect birth size, and pregnant women may be exposed to metal mixtures. Comprehensive studies analyzing the effects of combined metal exposure with accurate individual blood metal concentrations are limited. The current study investigated the associations between maternal metal exposure and birth size in a large, nationwide Japanese cohort using individual and mixed model approaches. Methods: Lead, cadmium, mercury, selenium, and manganese blood concentrations were measured in pregnant women in the Japan Environment and Children's Study (JECS). Measurements of infant birth size—including body weight, body length, and head and chest circumference—were collected. Linear and logistic regressions were used for birth size measurements and the odds of an infant being small in size for gestational age, respectively. Associations between combined metal mixtures and measurements at birth were evaluated using quantile g-computation and Bayesian kernel machine regression (BKMR). Results: Of the 103, 060 JECS pregnancies, 93, 739 mother–infant pairs were analyzed. The linear regression models showed that lead, selenium, cadmium, and manganese—but not mercury—were associated with body weight. Cadmium was associated with length and chest circumference and mercury was associated with head circumference. Quantile g-computation revealed that manganese increased infant birth weight, length, head circumference, and chest circumference. Lead was the strongest negative factor for infant birth weight, length, head circumference, and chest circumference. The BKMR analysis revealed that the metals had an additive, rather than a synergistic effect. Conclusion: Metal exposure is associated with infant birth size, with lead and manganese playing a more significant role in Japan. The effects of prenatal combined metal exposure at low levels warrant public health attention.